IMPLEMENTASI AKAD ISTISHNA PADA SISTEM PRE-ORDER JUAL BELI ONLINE - Nur Yessi Maryam; Risma Ayu Nurhabni; M. Masrukhan (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
Technological advancements have significantly simplified transactions, making it easier for people to shop online. E-commerce, defined as the buying and selling of products via the internet, has become a common practice in this digital age.. As an example, consider e-commerce, which refers to the online purchase and sale of products over the internet. Islamic law established for consumers and sellers when it comes to purchasing and selling. An online purchasing and selling system allows items to be pre-ordered and paid either fully or partially at the beginning, during, or at the end of the transaction, with an agreed grace period until the delivery is completed. The estimated waiting time has been reached. The pre-order system is one of muamalah’s innovative transaction mecanisms. This can be used for online purchases and sales. Online buying and selling is the process of purchasing, ordering, and paying in advance, in the middle or at the end, with a grace period. The purpose of this scientific paper is to investigate the istishna contract in this transaction in further detail. In this study, a descriptive strategy is blended with qualitative technique. Field research and literature reviews were undertaken in real life. Field study is a process finding out exactly and precisely